2018
DOI: 10.1101/481176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Habitat loss-induced tipping points in metapopulations with facilitation

Abstract: Habitat loss is known to pervade extinction thresholds in metapopulations. Such thresholds result from a loss of stability that can eventually lead to collapse. Several models have been developed to understand the nature of these transitions and how are they affected by the locality of interactions, fluctuations, or external drivers. Most models consider the impact of grazing or aridity as a control parameter that can trigger sudden shifts, once critical values are reached. Others explore instead the role play… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…The positive solution starts at a value z * = Σ defining the minimal (critical) population size. This result is related to those found within the context of extinction thresholds in metapopulation models due to habitat loss and fragmentation including continuous (Bascompte and Solé 1996) and first-order (Sardanyés et al 2019) transitions. It thus connects the problem of reduced habitat and the persistence of viral associations requiring higher-order interactions (such as mutualism).…”
Section: The Evolutionary Dimension: Multipartite Viruses and Musupporting
confidence: 79%
“…The positive solution starts at a value z * = Σ defining the minimal (critical) population size. This result is related to those found within the context of extinction thresholds in metapopulation models due to habitat loss and fragmentation including continuous (Bascompte and Solé 1996) and first-order (Sardanyés et al 2019) transitions. It thus connects the problem of reduced habitat and the persistence of viral associations requiring higher-order interactions (such as mutualism).…”
Section: The Evolutionary Dimension: Multipartite Viruses and Musupporting
confidence: 79%
“…S6(a)-(b)). These transients are typically found in systems with strong feedbacks e.g., cooperation, such as catalytic hypercycles (see e.g., [32, 33]) or metapopulations with facilitation [41]. Also, this dynamical delay tied to saddle-node bifurcations has been recently described in both deterministic and stochastic well-mixed approaches for the non-terraformed system explored in this article (see [46] for more details).…”
Section: Models and Resultsmentioning
confidence: 85%
“…Also, facilitation processes (involving strong nonlinearities) are known to introduce important changes in spatial systems, as compared to well-mixed ones. In this sense, recent research has found a shift from catastrophic tipping points to continuous ones due to local spatial processes [41, 47].…”
Section: Models and Resultsmentioning
confidence: 99%
See 2 more Smart Citations